PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI MASA PANDEMI COVID-19: Survei Pada Konsumen Baju Koko Purnama Kawalu Kota Tasikmalaya - Ricardo Prambudi; Cece Rakhmat; Ari Arisman (Melati Institute, 2022)
This study aims to determine and analyze the influence of Digital Marketing on Consumer Purchase Decisions Koko Purnama Kawalu Tasikmalaya. The method used is a survey method, with a population of consumers of Baju Koko Purnama Kawalu Tasikmalaya who have shopped online through the Instagram platform of Baju Koko Purnama Kawalu Tasikmalaya, which is then taken as a consumer sample of 80 respondents. The research method used is a quantitative descriptive approach. The data analysis tool uses simple linear regression, the coefficient of determination and the correlation coefficient. Data collection techniques using questionnaires to respondents who became the sample. The results showed that Digital Marketing had a positive and significant effect on Consumer Purchase Decisions for Koko Purnama Kawalu Tasikmalaya.